High Performance Polymers - Polyimides Based - From Chemistry to Applications - Marc J.M. Abadie (IntechOpen, 2012)
The feature of polyimides and other heterocyclic polymers are now well-established and used for long term temperature durability in the range of 250 - 350'C. This book will review synthesis, mechanisms, ultimate properties, physico-chemical properties, processing and applications of such high performance materials needed in advanced technologies. It presents interdisciplinary papers on the state of knowledge of each topic under consideration through a combination of overviews and original unpublished research. The volume contains eleven chapters divided into three sections: Chemistry; Chemical and Physical Properties; and Applications.
English
Keywords: Physical Sciences; Engineering and Technology; Materials Science; Biochemistry; Polymers